The incomplete text and the ardent core: the role of unfulfilment in the work of Vladimir Nabokov - Madocks, Rodney (1980)
Three related elements of Nabokov's art are introduced at the beginning of the study: Nabokov's monist philosophy and the self-contained structures of his art, the necessity of the co-operation of the reader to bring the 'objective existence' of the novel into being and lastly the development of the consciousness as the measure of his characters in relation to the master consciousness Nabokov. All three of these elements are shown to depend on a law of unfulfilment operating in his work, which always seeks to match one mode with its provisional opposite. The abstract basis of this idea is then explained in terms of Nabokov's use of mirror images which (it is shown) educates the reader by teaching him what not to do before he can fully experience Nabokov's deeper structures. The three-fold mirror basis of his work (the artist - the work - the reader) is next related to the tripartite Hegelian method of philosophy. Hegel's ideas are shown to be explainable in mirror terms and the accordance between both writers is demonstrated. The unfulfilling theme is identified with the antithetic phase of the syllogism. These Hegelian and mirror insights are then applied to two novels: The Gift and The Real Life of Sebastian Knight. The conclusion seeks to define the experience of the reader's apprehension of Nabokov's art using the Hegelian vocabulary that has been developed. This study demonstrates that Nabokov evolved an informal yet developed metaphysic which must be understood as an avenue to the meaning of his art. The three-fold Hegelian formula, arrived at through the discovery of the role of unfulfilment in his work, provides the Nabokov reader with an indispensable key to the solution of Nabokov' s "riddles with elegant solutions".